2021
DOI: 10.1002/ece3.8100
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic microbial studies in diverse populations of Aphis gossypii, existing on altered host plants in different localities during different times

Abstract: The cotton aphid, Aphis gossypii Glover, is an important global pest that sucks sap and transmits viral diseases to host plants, causing serious economic losses in agriculture (Figure 1) (Blackman & Eastop, 2000). It colonizes more than 600 plant species, many of which are important crops (Ebert & Cartwright, 1997). Plant transfer experiments and genetic diversity analysis have highlighted the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Although Arsenophonus and Sodalis are among the symbionts most frequently observed in arthropod hosts including psyllid lineages ( Thao et al , 2000a ; Spaulding and von Dohlen, 2001 ; Hansen et al , 2007 ; Moran et al , 2008 ; Sloan and Moran, 2012 ; Arp et al , 2014 ; Hall et al , 2016 ; Morrow et al , 2017 ; Nakabachi et al , 2022a , 2022b ), Symbiopectobacterium is the lineage identified for the first time in Psylloidea. Arsenophonus have been found in diverse insect groups, including wasps ( Gherna et al , 1991 ; Nadal-Jimenez et al , 2023 ), bees (Hymenoptera: Apoidea) ( Nadal-Jimenez et al , 2022a ), aphids ( Russell et al , 2003 ; Wulff and White, 2015 ; Tian et al , 2019 ; Zhang et al , 2021 ; Yorimoto et al , 2022 ), psyllids ( Spaulding and von Dohlen, 1998 , 2001 ; Subandiyah et al , 2000 ; Thao et al , 2000a ; Hansen et al , 2007 ; Hall et al , 2016 ; Morrow et al , 2017 ; Nakabachi et al , 2022a , 2022b ), whiteflies ( Thao and Baumann, 2004 ; Chiel et al , 2007 ; El Hamss et al , 2021 ), triatomine bugs (Hemiptera: Heteroptera) ( Hypsa and Dale, 1997 ), lice (Psocodea: Anoplura) ( Sasaki-Fukatsu et al , 2006 ; Allen et al , 2007 ; Kirkness et al , 2010 ), louse flies ( Dale et al , 2006 ; Nováková et al , 2009 , 2016 ), and ticks (Arachnida: Ixodida) ( Grindle et al , 2003 ). The types of symbiotic relationships with hosts exhibit a wide diversity from parasitism ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although Arsenophonus and Sodalis are among the symbionts most frequently observed in arthropod hosts including psyllid lineages ( Thao et al , 2000a ; Spaulding and von Dohlen, 2001 ; Hansen et al , 2007 ; Moran et al , 2008 ; Sloan and Moran, 2012 ; Arp et al , 2014 ; Hall et al , 2016 ; Morrow et al , 2017 ; Nakabachi et al , 2022a , 2022b ), Symbiopectobacterium is the lineage identified for the first time in Psylloidea. Arsenophonus have been found in diverse insect groups, including wasps ( Gherna et al , 1991 ; Nadal-Jimenez et al , 2023 ), bees (Hymenoptera: Apoidea) ( Nadal-Jimenez et al , 2022a ), aphids ( Russell et al , 2003 ; Wulff and White, 2015 ; Tian et al , 2019 ; Zhang et al , 2021 ; Yorimoto et al , 2022 ), psyllids ( Spaulding and von Dohlen, 1998 , 2001 ; Subandiyah et al , 2000 ; Thao et al , 2000a ; Hansen et al , 2007 ; Hall et al , 2016 ; Morrow et al , 2017 ; Nakabachi et al , 2022a , 2022b ), whiteflies ( Thao and Baumann, 2004 ; Chiel et al , 2007 ; El Hamss et al , 2021 ), triatomine bugs (Hemiptera: Heteroptera) ( Hypsa and Dale, 1997 ), lice (Psocodea: Anoplura) ( Sasaki-Fukatsu et al , 2006 ; Allen et al , 2007 ; Kirkness et al , 2010 ), louse flies ( Dale et al , 2006 ; Nováková et al , 2009 , 2016 ), and ticks (Arachnida: Ixodida) ( Grindle et al , 2003 ). The types of symbiotic relationships with hosts exhibit a wide diversity from parasitism ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesize that the nutrients provided by Buchnera are required by Arsenophonus and that the reduction in Arsenophonus may also be the reason for the decrease in A. gossypii eggs. Serratia is a common facultative symbiotic bacterium in A. gossypii which improves host adaptability and heat tolerance [50]. Zhou et al found that in pea aphids, Serratia can promote aphid host growth and development by enhancing fatty acid biosynthesis [51].…”
Section: Discussionmentioning
confidence: 99%
“…As the physical proximity of symbionts and their degree of anatomical integration into the host are possible indications of metabolic functions and cooperation between nutritional symbionts ( Renoz et al., 2022 ; A et al., 2023 ; Michalik et al., 2023 ), these aspects should be examined to complement genome-based metabolic inferences using, for example, fluorescent in situ hybridization (FISH) approaches. In addition, aphids can often host more than one facultative symbiont, sometimes up to four ( Renoz et al., 2020 ; Zhang et al., 2021 ). It is important to determine how such a large number of bacterial associates are spatially arranged relative to each other within the aphid host in order to correlate tissue tropism with potential metabolic interactions.…”
Section: Current Research and Perspectivesmentioning
confidence: 99%